A1_3 Hydrogen Atom in One Dimension - Li, Leonard; Wu, Tong; Hophuong, Ocean; Warford, Louis (Physics Special Topics, 2017)
We investigated the ground state energy of the hydrogen atom if it existed in a world with only one spatial dimension. Using variational principle, we found that the ground state energy of a 1D hydrogen atom is less than or equal to 0.17 eV.